Modified exponentiated inverted exponential distribution with applications to life time dataset - Chaudhary, Arun Kumar; Sah Telee, Lal Babu (NCC Journal, 2022)
In this article, we have introduced a new probability distribution called Modified Exponentiated Inverted Exponential (MEIE) Distribution. The introduced model is right tailed increasing- decreasing hazard rate function. We have discussed some statistical properties like probability density function, cumulative distribution function, survival function and hazard rate function etc. Model parameters are estimated via Maximum Likelihood, Least Squares, and Cramer-Von Mises estimation techniques. To check the applicability a real data set is taken and the model validation is checked using different information criteria as well as using some graphical techniques. For model comparison we have considered some published probability model.